Achieving a Large Energy Gap in Bi(110) Atomically Thin Films - Yuan, Qing; Li, Yafei; Guo, Deping; Lou, Cancan; Cui, Xingxia; Mei, Guangqiang; Jiao, Chengxiang; Huang, Kai; Hou, Xuefeng; Ji, Wei; Cao, Limin; Feng, Min (Small structures, 2023)
Metal–insulator transition has long been one of the key subjects in condensed matter systems. Herein, the emergence of a large energy gap (Eg, 0.8–1.0 eV) in Bi(110) two‐atomic‐layer nanoribbons grown on a SnSe(001) substrate is reported, which normally has an intrinsic semimetal‐like characteristic. The existence of this abnormally large Eg in Bi(110) is, however, determined by Bi coverage. When coverage is above ≈64 ± 2%, Eg vanishes, and instead, a Bi(110) semimetal‐like phase appears through a singular insulator–metal transition. Measurements using qPlus atomic force microscopy demonstrate that either insulating or semimetal‐like Bi(110) possesses a distorted black phosphorous structure with noticeable atomic buckling. Density function theory fully reproduces the semimetal‐like Bi(110) on SnSe(001). However, none of the insulating phases with this large Eg could be traced. Although the underlying mechanism of the large Eg and the insulator‐metal transition requires further exploration, experiments demonstrate that similar results can be achieved for Bi grown on SnS, the structural analog of SnSe, exhibiting an even larger Eg of ≈2.3 eV. The experimental strategy may be generalized to utilization of group‐IV monochalcogenides to create Bi(110) nanostructures with properties unachievable on other surfaces, providing an intriguing platform for exploring the interesting quantum electronic phases. We report the emergence of a large energy gap (Eg) in Bi(110) two‐atomic‐layer nanoribbons grown on SnSe(001) and SnS(001), which normally are semimetals. The abnormal Eg vanishes, however, when the coverage of Bi reaches a critical value, and instead, a semimetal‐like phase appears. The experimental strategy may be generalized to group‐IV monochalcogenides to create quantum materials with properties unachievable on other surfaces.